The evolving role of molecular profiling in prostate cancer: basal and luminal subtyping transcends tissue of origin - Mian, Omar Y.; Tendulkar, Rahul D.; Abazeed, Mohamed E. (Translational Cancer Research, 2017)
Prostate cancer is the second most common cancer in men worldwide, accounting for 15% (1.1 million) of the total new male cancer cases and 6.6% (307,000) of the total cancer deaths in men (1). In the U.S., 161,360 new cases and 26,730 deaths from prostate cancer are estimated for 2017 (2).